Pengaruh Konsumsi Makanan Kariogenik dan Kebiasaan Menyikat Gigi Terhadap Kejadian Karies Gigi Molar Pertama Permanen Pada Anak Usia 9-11 Tahun di SDN Blimbing 01 Kecamatan Gatak Kabupaten Sukoharjo - Sribintari, Eva Dian; , drg. Ana Riolina, MPH; , drg. Naviatullaily Yarsiska (2016)
The first molars permanent are first permanent teeth that grow at the age 6-7 years old with deep pit and fissure become get risk to be caries due to lack knowledge and awareness of children and parents in care. Caries in children are caused by children liked consume cariogenic foods that are sweet and sticky and their habits of tooth brushing are not correct. Cariogenic food with sticky consistency difficult to remove from the surface of the tooth and the carbohydrates are easy to fermented by bacteria which can dissolve tooth structure and lead to caries. The purpose of this study was to determine the effect of cariogenic food consumption and habits of brushing teeth to influence of first permanent molar caries in 9-11 years children on SD N Blimbing 01 gatak district sukoharjo . The method is the observational with cross sectional. Respondents were students aged 9-11 years in SD Blimbing 01. This study have been held in May 2016. Sampling technique using stratified random sampling. Respondents were interviewed for 7 days to determine the frequency of cariogenic foods for a week, then respondents were instructed to brush their teeth and did the assessment. Furthermore, the examination of the first permanent molar to see events of caries. This study tested using the kruskal-wallis test and obtained the value of p = 0.000 (p <0.05). Thus it can be concluded that the consumption of foods cariogenic, teeth brushing habits, consumption of food cariogenic and teeth brushing habits have influenced to the dental caries. Keywords: dental caries, the first permanent molars, cariogenic foods, brushing teeth.